2015
DOI: 10.1080/00221686.2015.1040086
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic design of baffles in disinfection contact tanks

Abstract: This study focuses on understanding the hydraulic design of baffled contact tanks using computational fluid dynamics simulations. In particular, we address the key question: for a given footprint of a rectangular tank with a specified inlet width (W inlet ), how does the hydraulic efficiency of a baffled tank depend on the configuration of internal baffles? In an effort to address this question, a carefully conceived parametric study consisting of 30 high-resolution two-dimensional (planar) simulations was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Some researchers have suggested that the ratio between baffle opening length and the channel width can influence BE values, with the optimal baffle opening length–to–channel width ratio being 1.0 (Taylor, Carlston, & Venayagamoorthy, ). This does not appear to be a factor in this study because most of the plants were designed with baffle opening length‐to‐channel width ratios that were near or equal to 1.0, with only four of the treatment plants having a ratio not within the 0.8–1.2 range.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have suggested that the ratio between baffle opening length and the channel width can influence BE values, with the optimal baffle opening length–to–channel width ratio being 1.0 (Taylor, Carlston, & Venayagamoorthy, ). This does not appear to be a factor in this study because most of the plants were designed with baffle opening length‐to‐channel width ratios that were near or equal to 1.0, with only four of the treatment plants having a ratio not within the 0.8–1.2 range.…”
Section: Resultsmentioning
confidence: 99%
“…Two baffles were used to limit cost and allow for ease of construction. Baffle orientation, spacing, and length were selected using recommendations from previous research (Taylor et al 2015, Taylor 2012). Figure 3, part A, shows a planview schematic of the baffled system and Figure 3, part B, shows the fully constructed prototype.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Several investigations have been carried out to evaluate contact tank design and efficiency [13][14][15][16][17][18]. It has been shown that throughput of contact tanks can be improved by simple geometrical modifications, such as the 3 insertion of baffles or guiding walls [19][20][21]. Unfortunately, such changes do not always bring the tank behavior enough close to plug flow.…”
Section: Introductionmentioning
confidence: 99%